Global burden of lower respiratory infections attributable to PM2.5 across global, regional, national level and China from 1990 to 2021 and predictions to 2035: A cross-sectional study - Enhao Wang; Shazhou Li; Ying Wu; Huihui Liu; Yang Li; Tao Zhou (Ecotoxicology and Environmental Safety)
Background: Particulate matter (PM) based air pollution closely linked to lower respiratory infections (LRIs). PM2.5 air pollution is identified as the leading risk factor for LRIs. This study examined deaths and disability-adjusted life years (DALYs) associated with PM2.5-related LRIs to understand and prevent their impact. Methods: Using Global Burden of Disease Study 2021 data, we analyzed PM2.5's effects on LRIs globally, regionally, and in China across different socio-demographic index (SDI) regions. Autoregressive integrated moving average (ARIMA) modeling predicted 15-year trends in age-standardized mortality rates (ASMR) and disability-adjusted life year rates (ASDR). Results: PM2.5 contributed to 0.65 million deaths and 29.1 million DALYs from LRIs in 2021. An inverse relationship existed between PM2.5-related LRIs and SDI, with males showing higher vulnerability. Age-specific rates followed a V-shaped distribution in global and lower SDI regions. Mortality peaked in those over 95, while DALYs were highest in children under 5. ASMR and ASDR projections show slight decreases over 15 years. China's burden approaches high-middle SDI levels. Conclusions: Higher SDI areas show lower disease burden, while PM2.5-related LRIs remain substantial in lower SDI regions. This necessitates targeted preventive strategies for vulnerable populations, particularly in less developed regions.